2021
DOI: 10.3390/languages6010031
|View full text |Cite
|
Sign up to set email alerts
|

L2 Knowledge of the Obligatory French Subjunctive: Offline Measures and Eye Tracking Compared

Abstract: Extensive research has shown that second language (L2) learners find it difficult to apply grammatical knowledge during real-time processing, especially when differences exist between the first (L1) and L2. The current study examines the extent to which British English-speaking learners of French can apply their grammatical knowledge of the French subjunctive during real-time processing, and whether this ability is modulated by the properties of the L1 grammar, and/or proficiency. Data from an acceptability ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In a recent study, Dudley and Slabakova [ 113 ] used eye tracking (factors inspected: eye fixations, convergence, and saccades) to investigate online sensitivity to the subjunctive in French L2. Forty-five English-speaking learners of French (34 females, mean age = 14.42, SD = 1.12 years, first exposure to French at 9.47 years) in their second and final year of an undergraduate degree or their one-year postgraduate degree in modern and foreign languages took part in the study.…”
Section: The French Subjunctive As An Example Of Linguistic Complexit...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Dudley and Slabakova [ 113 ] used eye tracking (factors inspected: eye fixations, convergence, and saccades) to investigate online sensitivity to the subjunctive in French L2. Forty-five English-speaking learners of French (34 females, mean age = 14.42, SD = 1.12 years, first exposure to French at 9.47 years) in their second and final year of an undergraduate degree or their one-year postgraduate degree in modern and foreign languages took part in the study.…”
Section: The French Subjunctive As An Example Of Linguistic Complexit...mentioning
confidence: 99%
“…The research questions sought to determine whether sensitivity was modulated by L1–L2 differences in verbal mood featural formal configurations and whether the level of proficiency performed a role in the detection of errors involving subjunctive use. Results from the acceptability judgment task showed that participants had knowledge of the French subjunctive but were unable to apply their knowledge when reading the sentences [ 113 ]. The eye-tracking test failed to demonstrate any evidence regarding the L2 learners’ sensitivity to mood mismatches (violation paradigm).…”
Section: The French Subjunctive As An Example Of Linguistic Complexit...mentioning
confidence: 99%